(untitled) (Journal of Hama University, 2025)
The aim of this study was to investigate the effect of utilization of Japanese quail egg yolk in cooled semen extender of cattle bulls. The experiment was conducted at the Al-Ghazlaniyah Artificial Insemination Center in the Damascus countryside. Eight mature bulls of Friesian and Shami were used in the experiment, divided into two groups (4 bulls in each group), this study was done during the period from 15\10\2022 to 15\12\2022. Semen samples were collected once a week using an artificial vagina. Immediately after semen collection, semen samples were evaluated and only the ejaculates that showed total motility (> 70 %) were used. The semen samples were pooled for each group (Friesian, Shami), and diluted using Tris-fructose extender. Different concentrations of Japanese quail egg-yolk (QEY), T2 (5%) and T3 (10%) were added, and the T1 (10%) concentration of chicken egg-yolk (CEY) was considered the (control group). Extend semen samples were stored at 5 °C for 4 days. After incubation at (37°C), some semen indicators were determined (percentage of individual motility and sperm membrane integrity). The hypoosmotic swelling test (HOST) was used to evaluate sperm membrane integrity. In both groups (Friesian and Shami), the results showed d that using Japanese quail egg-yolk at a concentration of (5%) T2 led to significant increase (P<0.05) in the percentage of individual motility and the percentage of sperm with an intact plasma membrane, and there was non-significant differences (p>0.05) between T2 QEY and control treatment T1 (10%) chicken egg-yolk (CEY). The results showed that there were significant decrease (P<0.05) in the percentages of individual motility and sperm membrane integrity in T3 (10%) QEY comparison to T2 (5%) QEY and T1 (10%) CEY (Control group). As for effect of preservation duration, the results showed a significant decrease (P<0.05) in the percentage of individual motility and sperm membrane integrity in all treatments (T1, T2, T3) on the 4th day of storage at 5°C. The decrease in the studied indicators was greater in treatment (T3) QEY comparison to (T1) CEY and (T2) QEY. We conclude from the above that adding QEY at a concentration of (5%) and adding CEY at a concentration of (10%) was better than adding QEY at a concentration of (10%) in the semen extender of Friesian and Shami bulls during storage at 5°C up to 4 days.